2019
DOI: 10.1038/s41586-019-1304-2
|View full text |Cite
|
Sign up to set email alerts
|

Spin–orbit-driven band inversion in bilayer graphene by the van der Waals proximity effect

Abstract: Spin orbit coupling (SOC) is the key to realizing time-reversal invariant topological phases of matter [1, 2]. Famously, SOC was predicted by Kane and Mele[3] to stabilize a quantum spin Hall insulator; however, the weak intrinsic SOC in monolayer graphene [4][5][6][7] has precluded experimental observation. Here, we exploit a layer-selective proximity effect-achieved via van der Waals contact to a semiconducting transition metal dichalcogenide[8-21]-to engineer Kane-Mele SOC in ultra-clean bilayer graphene. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
166
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(184 citation statements)
references
References 33 publications
15
166
0
Order By: Relevance
“…4). Previous works established that WSe 2 can induce large SOI of both Ising and Rashba type into monolayer and bilayer graphene 15,16 , and it is therefore reasonable to assume that the SOI is similarly generated in the upper (proximitized) layer of TBG in our devices. Continuum-model calculations taking into account this effect show that the SOI lifts the degeneracy of both flat and dispersive bands, thereby breaking four-fold spin-valley symmetry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4). Previous works established that WSe 2 can induce large SOI of both Ising and Rashba type into monolayer and bilayer graphene 15,16 , and it is therefore reasonable to assume that the SOI is similarly generated in the upper (proximitized) layer of TBG in our devices. Continuum-model calculations taking into account this effect show that the SOI lifts the degeneracy of both flat and dispersive bands, thereby breaking four-fold spin-valley symmetry.…”
mentioning
confidence: 99%
“…This mismatch implies that the moiré pattern formed between TBG and WSe 2 has a maximum lattice constant ∼ 1 nm, in other words, much smaller than that formed in small-angle TBG (> 10 nm). Second, it is well-established that WSe 2 can induce a spin-orbit interaction (SOI) in graphene via van der Waals proximity 15,16 . And finally, due to hybridization effects, WSe 2 may also change both the Fermi velocity of the proximitized graphene sheet and the system's phonon spectrum.…”
mentioning
confidence: 99%
“…At the Gr/TMD interface, the spatial inversion symmetry is broken, and the graphene sublattices having K(K') valleys experience different crystal potentials and spin-orbit coupling magnitudes from the underlying TMD. The electron-spin degree of freedom and its interaction with other properties such as valley pseudospins in the presence of SOC provide access to spintronic phenomena such as spin-valley coupling [4][5][6][7]9], spin-Hall effect [10,11], (inverse) Rashba-Edelstein effect [12][13][14][15][16] and even topologically protected spin-states [17][18][19][20][21] which are not possible to realize in pristine graphene. The mentioned effects are sought after for realizing enhancement and electric field control of SOC [1,4,8,[22][23][24][25], efficient charge-current to spincurrent conversion and vice versa [10,[27][28][29], which will be the building blocks for developing novel spintronic applications [13,30].…”
mentioning
confidence: 99%
“…For the non‐AB‐stacked bilayer graphene, the top layer is rotated with respect to the bottom layer in a twisted angle (Figure b) and the electronics structures are dependent on the twisted angles. Different twist angles (stacking order) can form different bilayer graphene with different physical properties . MacDonald and Bistritzer suggested that the electronic properties of twisted bilayer graphene (TBG) are very sensitive to the relative orientation of its layers.…”
Section: Introductionmentioning
confidence: 99%